1996
DOI: 10.1063/1.115693
|View full text |Cite
|
Sign up to set email alerts
|

Optical investigations of the dynamic behavior of GaSb/GaAs quantum dots

Abstract: Time-resolved radiative recombination measurements on GaSb quantum dots have been performed. The GaSb quantum dots are grown by molecular beam epitaxy on ͑100͒ GaAs through a self-assembly process. Time-resolved measurements show that, after a rapid hole capture process, the photoluminescence decays with a fast and a slow component. The fast component is shortened significantly with higher excitation intensity while the slow component is roughly constant. The radiative lifetimes are much longer than the lifeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
100
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 11 publications
13
100
1
1
Order By: Relevance
“…A number of PL measurements have been published on GaSb dots made both in this laboratory 7 and others, 6,8 and they have associated a PL line at 1.14 eV with the recombination of an electron in the GaAs with a hole in the GaSb. This PL data is consistent with the DLTS reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of PL measurements have been published on GaSb dots made both in this laboratory 7 and others, 6,8 and they have associated a PL line at 1.14 eV with the recombination of an electron in the GaAs with a hole in the GaSb. This PL data is consistent with the DLTS reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Photoluminescence ͑PL͒ experiments have demonstrated that GaSb QDs are significantly different from In x Ga 1Ϫx As/GaAs QDs are they have a type II band structure with a well in the GaSb valence band, which captures holes, and a barrier in the conduction band, which prevents the capture of electrons. [6][7][8] This band structure may be useful in electronic devices, particularly those requiring charge storage.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial separation of electrons and holes in type-II structures results in long exciton lifetimes, [2][3][4] resulting in interesting applications for longwavelength optoelectronics. 5 The exclusive confinement of holes and their large localization energy makes GaSb/GaAs QDs particularly interesting for charge storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…5 The exclusive confinement of holes and their large localization energy makes GaSb/GaAs QDs particularly interesting for charge storage devices. [6][7][8] GaSb/GaAs QDs were first grown using molecular beam epitaxy 2,9 and later by metal-organic chemical vapor epitaxy, 10,11 followed by optical characterization, 9,[12][13][14][15] cross-section scanning electron microscopy investigations, 16 and deep-level transient spectroscopy (DLTS) studies, 17,18 accompanied by numerical calculations. [19][20][21] The various investigations have been performed on different samples.…”
Section: Introductionmentioning
confidence: 99%
“…19 The type-II blueshift was quantified in the fine structure of the rings' emission using two techniques: (i) applying a Lorentzian fit to individual exciton peaks and extracting the central position, and (ii) following a centre-of-mass (CoM) fitting procedure by integrating each µPL spectrum and calculating the point corresponding to the pixel value in which the half-area falls. The results of these two techniques are illustrated on top of the experimental data shown in Fig.…”
mentioning
confidence: 99%